2017
DOI: 10.18551/rjoas.2017-11.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Rubber Market System on Farmer’s Income in South Sumatra Province, Indonesia

Abstract: Indonesia is the second biggest natural rubber producer in the world; however its processed rubber has low quality and price. This is because the rubber plantation most cultivated by non estate plantation (smallholding plantation). Central government of Indonesia has developed some policies to overcome this problem and one of them is to establish the Processing and Marketing Unit of Rubber material or PMUR ('UPPB') since 2008. However until 2014 only a few farmers (around 5%) had sold their products with PMUR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Partner farmers will receive marketing guarantees/distribution results and have different price guarantees from non partnership farmers. This result is consistent with the research of Husin et al, (2017) which shows that partnership rubber farmers earn 68% of their income, much higher than 64% of non partnership farmers. This very significant difference is very beneficial for rubber farmers.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Partner farmers will receive marketing guarantees/distribution results and have different price guarantees from non partnership farmers. This result is consistent with the research of Husin et al, (2017) which shows that partnership rubber farmers earn 68% of their income, much higher than 64% of non partnership farmers. This very significant difference is very beneficial for rubber farmers.…”
Section: Resultssupporting
confidence: 92%
“…Production costs, fertilizer costs, average costs, marketing costs, rubber prices, net income and gross income are also different. As for the difference of opinion by Husin et al (2017), the income gap between farmers with and without partnership is significant. The income of partner farmers is more than that of non-partnered farmers.…”
Section: Introductionmentioning
confidence: 99%
“…The farmers' income of PMU members who applied auctions and partnerships was 53% and 64% larger than farmers in traditional marketing systems. However, incomes of either new marketing system are not significantly different (Husin et al, 2017). This study was supported by (Agustina et al, 2017) that organized marketing system has changed the quality of raw rubber produced by smallholders and increases the farmers' share as well.…”
Section: Literature Reviewsupporting
confidence: 57%
“…These data show that many smallholders still sell through non-PMU channel, especially within the traditional marketing system. However, many studies have found that income, price, and efficiency of PMU marketing channel were more profitable for smallholders than non-PMU marketing channel Herdiansyah, Nurmalina, &Winandi, 2015;Husin, Yulius, Dessy, & Antoni, 2017;Sujarwo, 2015;Syarifa, Agustina, Alamsyah, &Nugraha, 2016). Therefore this study aims to provide answers to the following research question: Which factors mainly affect smallholders' choice of a PMU or non-PMU marketing channel ?.…”
Section: Problem Statementsmentioning
confidence: 99%
See 1 more Smart Citation